Antibacterial and Anticancer Properties of New Fluoroquinolones - Al Rimawi, Maha R.; Al-Hiari, Yusuf M.; Al-Bakri, Amal G.; Bardaweel, Sanaa K. (Asian Journal of Chemistry, 2019)
Fluoroquinolones are clinically successful antibacterial agents. In this work a series of novel 7-substituted anilino-8-nitrofluoroquinolone esters (3-9), acids (10-16) and 8-amino reduced derivatives (17-23) of the later compounds were successfully prepared and characterized using spectroscopic techniques. All the compounds tested (10-23) showed good antibacterial activity against both Gram-positive and Gram-negative standard bacterial strains. Interestingly, 8-amino reduced derivatives (17-22) were more active against both standard strains than their 8-nitro acid analogues (10-15). Moreover, some targeted compounds have shown reasonable activity mainly against resistant gram positive bacteria. In particular compounds 10, 12 and 16 displayed a potent activity against methicillin resistant S. aureus (MRSA) with MIC values of 4.7, 2.3 and 1.2 μg/mL, respectively. Lipophilicity could be a plausible explanation of such higher activity against the gram positive resistant strain (MRSA). Biological screening of cytotoxic activity against five cancer cell lines using an in vitro cell culture system was achieved for all tested compounds. These derivatives have shown weak activity for most of them. Interestingly, more lipophilic nitroacids (10-15) were more active than their analogous reduced acids (17-22).